2021
DOI: 10.1155/2021/1246491
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins from Hibiscus syriacus L. Inhibit NLRP3 Inflammasome in BV2 Microglia Cells by Alleviating NF‐κB‐ and ER Stress‐Induced Ca2+ Accumulation and Mitochondrial ROS Production

Abstract: Anthocyanins from the petals of Hibiscus syriacus L. (PS) possess anti-inflammatory, antioxidant, and antimelanogenic activities. However, it remains unclear whether PS inhibit the NLR family pyrin domain-containing 3 (NLRP3) inflammasome activation and assembly. This study is aimed at investigating whether PS downregulate NLRP3-mediated inflammasome by inhibiting nuclear factor-κB (NF-κB) and endoplasmic reticulum (ER) stress. BV2 microglia cells were treated with PS in the presence of lipopolysaccharide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…While the specific mechanism as well as whether the effects are present in microglial mitochondria isn't clear, Kastl et a., found that TNF-α treatment on Hepa1-6 (mouse) and Huh-7 (human) liver cell lines in vitro, depolarized mitochondrial membranes, decreased ATP production, and increased ROS release. Similar mitochondrial deficits have been described in BV2 cells treated with LPS, indicating that cytokines produced by TLR activation may directly signal changes in mitochondria function and efficiency (Voloboueva et al, 2013;Molagoda et al, 2021). As previously mentioned, transient cytokine levels increase in the brain with age, thus posing a greater risk to mitochondrial heath.…”
Section: Aging As a Source Of Pre-tbi Mitochondrial Dysfunctionsupporting
confidence: 66%
“…While the specific mechanism as well as whether the effects are present in microglial mitochondria isn't clear, Kastl et a., found that TNF-α treatment on Hepa1-6 (mouse) and Huh-7 (human) liver cell lines in vitro, depolarized mitochondrial membranes, decreased ATP production, and increased ROS release. Similar mitochondrial deficits have been described in BV2 cells treated with LPS, indicating that cytokines produced by TLR activation may directly signal changes in mitochondria function and efficiency (Voloboueva et al, 2013;Molagoda et al, 2021). As previously mentioned, transient cytokine levels increase in the brain with age, thus posing a greater risk to mitochondrial heath.…”
Section: Aging As a Source Of Pre-tbi Mitochondrial Dysfunctionsupporting
confidence: 66%
“…In turn, black rice, as well as its active compounds, anthocyanins, have been studied for their anti-inflammatory properties, especially with regard to the inhibition of the NLRP3 inflammasome pathway. Anthocyanins from Hibiscus syriacus L. inhibited LPS/ATPinduced NLRP3 inflammasome by inhibiting the NF-κB signaling pathway and leading to the inhibition of IL-1β and IL-18 release [60]. Another study found that, C3G from black rice possessed anti-inflammatory properties in lipopolysaccharide-induced RAW 264.7 cells and carrageenan-induced inflammation in air pouches in BALB/c mice through the suppression of the proinflammatory cytokines, TNF-α and IL-1β, mechanistically via regulating NF-κB and MAPK activation [50].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intracellular concentration of this ion in conjunction with reduced levels of potassium activates the inflammasome pathway and causes the release of IL-18 and IL-1β through plasma membrane-resident Ca 2+ channels as TRPV2, TRPM2, TRPM7, and P2X7R (86). In addition, this role is further confirmed by the fact that suppressing the outflow of calcium through membrane receptors and preventing its overload in the endoplasmic reticulum through nigericin, ATP, and alum [ 79 ], inflammasome activation and L-1β maturation are inhibited. Through the ASICs (acid-sensing ion channels), plasma membrane-resident Ca 2+ channels, calcium entry is allowed from the extracellular environment inside the cell [ 80 ].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%